Hasht-Behesht Pavilion Isfahan Its Study as a Viewpoint - Mohammad Javad Bina; Ladan Etezadi (صفه)
Hasht Behesht Pavilion is one of the prominent structures among Dowlatkhaneh Gardens. It was located at the center of the Bolbol Garden. Although this Garden is now converted into a park with an entirely different design, it is still possible to trace the original relationship between the Pavilion and Garden through a field study accompanied by a review of relevant historic documents. This paper attempts to infer the modus operandi of the Pavilion functioning as an eminent viewpoint. To this end, first the qualities and roles of a viewpoint are defined. This is followed by a description of the Hasht-Behesht Pavilion and Bolbol Garden. The relationship between the Pavilion and Garden is then analyzed based on two extremes of ‘to see’ or ‘not to see’. This paper concludes with emphasizing that the Pavilion is designed in a manner that has made it a viewpoint par excellence. It thus defines the relationship between humans, architecture and environment in concordance with the principles of a traditional garden.